Implementasi Algoritma Zhu Takaok Pada Aplikasi Translator Bahasa Indonesia-Finlandia Berbasis Android - Seli Trisia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Education is one thing that is very important for one's life, education also plays a big role for the progress and development of a nation. A developed and large nation that is certainly supported by adequate quality education for its citizens. One of the countries that has the best education level in the world is Finland. Finland is currently in fifth place after Hong Kong. Continuing college education in Finland is the desire of many Indonesian students, especially through scholarships, because continuing education in Finland can gain a lot of knowledge that may be rarely found in Indonesia. String Matching is an algorithm used to speed up the search process for the desired word. String matching is divided into two, namely exact matching and heuristic or statistical matching. The string matching algorithm has often been used before as an example in the string matching process based on the data text equation, namely Brute Force. In this case, the brute force algorithm is chosen because this algorithm can be used to search strings or texts. Brute force algorithm is an algorithm to match patterns with all text between 0 and n-m to find the existence of patterns in text. With the development of technology today string matching can also be used in education. Education is one thing that is very important for one's life. To overcome the above problems the authors build an android-based application, namely the Indonesian-Finnish translator application. In the search tools the author implements the string matching algorithm namely zhu takaoka algorithm. The zhu takaoka algorithm is one of the best algorithms that can do the string matching process quickly because it shifts with bad characters for two text characters in a row from right to left.